Real time evaluation of weld quality in narrow groove pipe welding - Marmelo, Patricia C. (Cranfield University, 2012)
With the growth in pipeline installations all over the world, there is a great demand for highly productive and robust welding systems. Mechanised pipe welding has been developed over the last 50 years and the present focus is towards development of automated pipeline welding systems. Pipeline welding automation is aimed at reducing costs and improving the installation quality. To attain fully automated pipe welding systems there is a need to rely on sensors and controls systems to mimic human like capabilities, such as visual inspection, in real time. The key aim of this work is to develop and evaluate methods of automatic assessment of weld bead shape and quality during narrow gap GMAW of transmission pipelines. This implies that the measured bead profile will be assessed to determine whether the bead shape will cause defects when the subsequent pass is deposited. Different approaches have been used to conquer the challenge that is emulating human reasoning, all with different objectives in mind. In spite of extensive literature research performed, very little information was found concerning the real time determination and assessment of bead shape quality and none of it was reported to be applied successfully to the pipeline industry. Despite the continuous development of laboratory laser vision systems commercial ones have been on the market for decades, some specifically developed for the welding application. Laser vision sensor systems provide surface profile information, and are the only sensors which can satisfactorily measure bead profile on a narrow groove. In order to be able to use them to automatically assess weld bead shape and quality, a deep understanding of their characteristics and limitations needs to be achieved. Once that knowledge was attained it was then applied to determine the best sensor configuration for this purpose. After that the development of human like judgment algorithms were developed to accomplish the aim that was set. Empirical rules were obtained from an experienced welder regarding the acceptability of bead shapes and were then applied in the developed system with good results. To scientifically evaluate and determine the rules to use in this system, further experiments would be required. The output of the system developed showed very accurate, reliable and consistent results that were true to the external measurements and comparisons performed. The developed system has numerous applications in the pipeline industry and it could easily be implemented on commercial systems.
Keywords: Pulsed Gas Metal Arc Welding (GMAW-P); Pipeline Welding; Adaptive Control; Bead Shape; Laser Vision Sensor; Weld Quality; Seam Tracking; Multi-pass Welding